Management of rheumatic atrial fibrillation - Chin, Ashley (SA Heart Journal, 2017)
Thromboembolism, secondary to rheumatic atrial fi brillation, remains an important cause of stroke and systemic embolism in low and middle income countries. This review will highlight the pathogenesis of rheumatic atrial fibrillation and thromboembolism. The risk factors and prevention of thromboembolism, including management strategies of rheumatic atrial fibrillation, will also be discussed.